2010
DOI: 10.1002/cncr.25631
|View full text |Cite
|
Sign up to set email alerts
|

Number of metastases, serum lactate dehydrogenase level, and type of treatment are prognostic factors in patients with brain metastases of malignant melanoma

Abstract: ; on behalf of the Dermatologic Cooperative Oncology Group and the National Interdisciplinary Working Group on Melanoma BACKGROUND: This multicenter study aimed to identify prognostic factors in patients with brain metastases from malignant melanoma (BM-MM). METHODS: In a retrospective survey in 9 cancer centers of the German Cancer Society, 692 patients were identified with BM-MM during the period 1986 through 2007. Overall survival was analyzed using a Kaplan-Meier estimator and compared with log-rank analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
98
3
12

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 27 publications
5
98
3
12
Order By: Relevance
“…Table VI presents the values of average survival periods of patients with MBM depending on the KPS score, which were 5.9-6.3 months for KPS ≥ 70 and were definitely lower in patients with a poorer general performance (KPS < 70), where they varied from 1.8 to 3.8 months. The results based on the site's material are comparable with those presented with other authors [5,13,14,37,40,46]. The other, generally accepted prognostic factor is the number of MBM foci.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Table VI presents the values of average survival periods of patients with MBM depending on the KPS score, which were 5.9-6.3 months for KPS ≥ 70 and were definitely lower in patients with a poorer general performance (KPS < 70), where they varied from 1.8 to 3.8 months. The results based on the site's material are comparable with those presented with other authors [5,13,14,37,40,46]. The other, generally accepted prognostic factor is the number of MBM foci.…”
Section: Discussionsupporting
confidence: 87%
“…In this case also the site's experience was compared with the results published by other authors [1,5,13,14,37,40,46]. Some investigators point to the adverse prognostics significance of the presence of metastases outside the brain, in particular in the lungs, liver, spleen and adrenal glands, and, to a lesser degree, in the bones, lymph nodes and skin [5,6,8,30,31,[33][34][35][40][41][42]. In the site's own material, in a single-variance analysis, it was shown that the co-existence of the metastases in extracranial locations was an adverse prognostic factor, which was, however, not confirmed by the results of the multivariance analysis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…До недавнего времени прогноз пациентов с диссеминирован-ной меланомой, имеющих метастатическое поражение головного мозга, оставался крайне неблагоприятным с медианой продолжи-тельности жизни, не превышающей 2-4 мес [9,10]. Следует от-метить, что недостаточное количество результатов рандомизиро-ванных исследований, обусловленное сложностями набора одно-родных групп больных, не позволяет говорить об общепринятых стандартах лечения.…”
unclassified